THE EFFECT OF TEACHER PROFESIONAL ALLOWANCE AND JOB SATISFACTION TOWARD ORGANIZATIONAL COMMITMENT (A Study on Private Islamic Junior High Schools Teachers in Tangerang Regency) - Suderajat, Suderajat; Rojuaniah, Rojuaniah (IJOSMAS, 2021)
The purposes of this study were to examine the effect of teacher professional allowance toward organizational commitment, to examine the teacher professional allowance toward job satisfaction and to examine the effect of job satisfaction toward organizational commitment. This research was a quantitative research. The population and samples in this research were the teachers of private Islamic junior high schools receiving the professional allowance in the Districts of Balaraja, Sukamulya and Kresek of Tangerang Regency, Banten, with the total respondents of 130 people. It was a quantitative research using the questionaries given to the teachers. The data analysis method used was SEM (Structural Equation Modelling) with the results shown that the teacher professional allowance was able to increase the organizational commitment and the job satisfaction and that the job satisfaction was able to increase the organizational commitment.